Investigation of ion transport parameters and electrochemical performance of plasticized biocompatible chitosan-based proton conducting polymer composite electrolytes - M. Hadi, Jihad; Aziz, Shujahadeen B.; Saeed, Salah R.; Brza, Mohamad A.; Abdulwahid, Rebar T.; Hamsan, Muhamad H.; Abdullah, Ranjdar M.; Mohd F. Z., Kadir; Saifful Kamaluddin, Muzakir (MDPI, 2020)
In this study, biopolymer composite electrolytes based on chitosan:ammonium iodide:Zn(II)-complex plasticized with glycerol were successfully prepared using the solution casting technique. Various electrical and electrochemical parameters of the biopolymer composite electrolytes’ films were evaluated prior to device application. The highest conducting plasticized membrane was found to have a conductivity of 1.17 × 10−4 S/cm. It is shown that the number density, mobility, and diffusion coefficient of cations and anions fractions are increased with the glycerol amount. Field emission scanning electron microscope and Fourier transform infrared spectroscopy techniques are used to study the morphology and structure of the films. The non-Debye type of relaxation process was confirmed from the peak appearance of the dielectric relaxation study. The obtained transference number of ions (cations and anions) and electrons for the highest conducting sample were identified to be 0.98 and 0.02, respectively. Linear sweep voltammetry shows that the electrochemical stability of the highest conducting plasticized system is 1.37 V. The cyclic voltammetry response displayed no redox reaction peaks over its entire potential range. It was discovered that the addition of Zn(II)-complex and glycerol plasticizer improved the electric double-layer capacitor device performances. Numerous crucial parameters of the electric double-layer capacitor device were obtained from the charge-discharge profile. The prepared electric double-layer capacitor device showed that the initial values of specific capacitance, equivalence series resistance, energy density, and power density are 36 F/g, 177 Ω, 4.1 Wh/kg, and 480 W/kg, respectively.